2002
DOI: 10.1023/a:1017940724692
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: In this prospective study 244 consecutive patients presenting with typical and chronic signs of gastroesophageal reflux were included. Conventional 24-hr esophageal pH monitoring was carried out to establish the symptom association probability, the concordance index, and the symptom sensitivity index. The symptom association probability could be calculated in 110 patients (45%). Two groups were identified: group 1 had normal duration of esophageal acid exposure; subgroup la (nonsignificant symptom association … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…28,29 We and others have previously shown that the SAP performs better than the SI in predicting a successful outcome after antireflux therapy including antireflux surgery, and that it is useful in determining the association of other perceptive atypical symptoms such as chest pain to reflux events. 18,29–31 By convention, for the SI to be abnormal, ≥50% of symptoms need to be associated with reflux events, that is, the SI has to be ≥50%. Some investigators have suggested that 25% is a more clinically relevant cut-off value when addressing chronic cough.…”
Section: Discussionmentioning
confidence: 99%
“…28,29 We and others have previously shown that the SAP performs better than the SI in predicting a successful outcome after antireflux therapy including antireflux surgery, and that it is useful in determining the association of other perceptive atypical symptoms such as chest pain to reflux events. 18,29–31 By convention, for the SI to be abnormal, ≥50% of symptoms need to be associated with reflux events, that is, the SI has to be ≥50%. Some investigators have suggested that 25% is a more clinically relevant cut-off value when addressing chronic cough.…”
Section: Discussionmentioning
confidence: 99%